(untitled) (La U Investiga, 2023)
Intestinal intussusception consists of the invagination of a segment of the intestine into another intestinal segment that is close. The area that is often affected is the small intestine, but it is not ruled out that it occurs in the large intestine. The etiology is diverse, around 10% is idiopathic, while 80-90% is organic; when it affects the colon, malignant lesions must be ruled out; while the localization in the small intestine leads to benign lesions. There is no defined clinic for intussusception in adult patients, to confirm the diagnosis, the imaging study with the highest sensitivity and specificity is simple and contrasted abdominal tomography. The treatment of choice is surgical. The case of a patient with intestinal intussusception due to polyps is presented with a clinical radiological approach. The importance of contrasted tomography for convenient diagnosis is highlighted, finally the surgical procedures performed for the resolution of the case are described.